Coach Leadership and Achievement Motivation on Women Basketball Athletes Performance - Citta Dewi, Kadek Pratita; Rojuaniah, Rojuaniah (Al Makki Publisher, 2023)
This study aims to determine the effect of coach leadership and achievement motivation on the performance of professional women's basketball athletes. This research is expected to contribute to the knowledge of organizational management and also make a practical contribution to clubs for the successful planning and implementation of improving athlete performance through coach leadership and motivation factors. This study uses a survey method. Respondents in this study were professional women's basketball athletes from six basketball clubs who participated in the 2021 Srikandi Cup, namely 1) Merpati Bali, 2) Friends of Semarang, 3) Flying Wheel Makassar, 4) GMC Cirebon, 5) Jakarta Scorpio and 6) Tanago Friesian Jakarta with a total sample of 120 athletes. The analysis technique uses SEM-PLS analysis. The results of the study show that the coach's leadership has an impact on achievement motivation and the performance of professional women's basketball athletes. The existence of support from good coach leadership will increase the athlete's achievement motivation. High achievement motivation makes athletes have big goals to achieve, so that athlete performance becomes better. Achievement motivation mediates the influence of coach leadership on athlete performance. The results of this study have implications that coaches need to provide more support to athletes so that they are more motivated to excel, so that they are expected to bring out their best performance for the team.